Corrosion and viscous ash deposition of a rotary air preheater in a coal-fired power plant. (25th February 2017) - Chen, Heng; Pan, Peiyuan; Shao, Huaishuang; Wang, Yungang; Zhao, Qinxin
Highlights: Corrosion and viscous ash deposits of a rotary air preheater in a coal-fired boiler were studied. Corrosion and viscous ash deposition were caused by the condensation of H2 SO4 rather than NH4 HSO4 . The mechanisms of corrosion and viscous ash deposition were analyzed. The coupling formation model of corrosion and viscous ash deposition was proposed. Abstract: The corrosion and viscous ash deposition characteristics of a rotary air preheater were investigated. Deposit samples and corroded heat transfer elements were taken from the air preheater of a 300 MW coal-fired power plant in China and analyzed by X-ray fluorescence, X-ray diffraction and scanning electron microscope equipped with energy dispersive X-ray spectroscopy. The results show that the serious corrosion and viscous ash deposition were both caused by sulphuric acid condensation rather than ammonium bisulfate deposition. The mechanisms of corrosion and viscous ash deposition were discussed and the coupling formation model of corrosion and viscous ash deposition was proposed.